Modified thoracoscopic wedge resection of limited peripheral lesions in S10 for children with congenital pulmonary airway malformation: Initial single-center experience - Guo, Rui; Zhai, Yunpeng; Zhang, Shisong; Zhao, Huashan; Xu, Hongxiu; Lv, Longfei (Frontiers in Pediatrics, 2022)
Objective The present study aimed to evaluate the safety and feasibility of modified thoracoscopic wedge resection of limited peripheral lesions in the posterior basal segment (S10) in children with congenital pulmonary airway malformation (CPAM). Materials and methods We retrospectively analyzed the clinical data of children with CPAM who underwent thoracoscopic modified wedge resection at our institution from November 2020 to February 2022. The surgical method was as follows: we marked the external boundary of the lesion with an electric hook, dissected and retained the segmental vein between the lesion and normal lung tissue as the internal boundary, cut the arteries, veins, and bronchus entering the lesion, and cut and sealed the lung tissue between the internal and external boundaries with LigaSure™ to complete the modified wedge resection. Results A total of 16 patients were included, aged 3.8−70.0 months and weighing 6.5−21.0 kg. The intraoperative course was uneventful in all patients. The median operation time and intraoperative bleeding volume were 74 min (50−110 min) and 5 mL (5−15 mL), respectively. The median postoperative drainage tube indwelling time was 3 days (2−4 days), and the median postoperative hospital stay was 6 days (4−8 days). Pathological diagnosis included two cases of type 1, 10 cases of type 2, and four cases of type 3 CPAM. There were no cases of intraoperative conversion, surgical mortality, or major complications. However, subcutaneous emphysema occurred in two children, which spontaneously resolved without pneumothorax orbronchopleural fistula development. All patients were followed up for a median period of 10 months (3–18 months), and there were no cases of hemoptysis or residual lesions on chest computed tomography. Conclusion Modified thoracoscopic wedge resection via the inferior pulmonary ligament approach is safe and feasible for children with CPAM with limited peripheral lesions in S10.